THE MYTHOLOGICAL ELEMENTS IN “ACAİBÜ’L MAHLUKAT”, “TERCÜME-İ MİFTAH CİFRÜ’L-CAMİ” AND “AHVÂL-İ KIYÂMET” OPUSSES IN PICTORAL EXPRESSION - Yüksel GÖĞEBAKAN (Fırat University, 2019)
The approach of recognition, understanding and conversion at the same time for humans is interpreted as a requirement for His being. Running across to supernatural difficulties human, lives a period of struggle along his life. At this period of struggle as a result of facing difficulties while looking for a solution, he consubstantiates all these events that happened with Gods, carries all of the unknowns into a metaphysical universe. He goes into a way of producing numberless legends after these consubstantiates were done. Maybe this situation is seen as the easiest way for himself. With this way, the human creates a source of comfort in a way for himself, putting his desperation against life on solid basis. The rich Turkish mythology taking its main facts from the geographical, climatic and cultural facts of Middle Asia and from cultures of the civilization that lived in Anatolia had been revealed as a result of such concerns. This richness being just special to Turkish mythology had showed itself at pictorial crafts which had showed improvements by growing, maturing and interacting at every period of time. At the mythological facts belonging to former historical terms, it was mentioned that a regression had been lived through with the acceptance of Islam, it was possible to see characteristic mythological specialities. Especially a few books written about miniature paintings had put forward a lot of visuals about these. At this study,the mythological facts were considered at the opuses of Acaibü’l Mahlukat, Tercüme-i Miftah Cifrü’l-Cami and Ahvâl-i Kıyâmet has great importance among the resources mentioned.